Pediatric glucose regulation without pre-meal insulin boluses: an approach based on switched control and time-varying IOB constraints - Fushimi, Emilia (2020)
Arti cial pancreas (AP) systems have shown to improve glucose regulation in type 1 diabetes (T1D) patients. However, full closed-loop performance remains a challenge particularly in children and adolescents, since these age groups often present the worst glycemic control. In this work, a new algorithm based on switched control and time-varying insulin-on-board (IOB) constraints is presented (ARGAE). This method is a combination of ideas from the previously introduced Automatic Regulation of Glucose (ARG) algorithm, which features no pre-meal insulin boluses, and the Amplitude Enable (AE) mode, which allows the controller to act more aggressively at the beginning of meal intake without risking postprandial hypoglycemia. The proposed control strategy is evaluated in silico and its performance contrasted with the ARG algorithm in the pediatric population. Results show that the ARGAE presents improved performance compared to the ARG algorithm even in presence of misclassi ed meals. Thus, future in vivo testing will involve the AE con guration.